Территориальное поведение четырехпятнистой стрекозы (Libellula quadrimaculata) (Odonata, Anisoptera) - Мокрушов, П.А. (Вестник зоологии, 1982)
The territory size guarded by the male of Libellula quadrimaculata during герго- ductive period depends on the rivals density in a pool. The larger si d r a g o n fl y popula- tion, the smaller is the guarded area. When population density exceeds the threshold value of 2-3 individuals per square meter. two groups of males appear: territorial and n o n - t e r r i t o r i a l . Territorial benaviour at nigh population density IS characterized with short chasing flights a n dprolonged periodsof perching; a t low density they guard over their territories in hovering flight. A possiblerole o foptical signs in the choice of an appropriate zone in the pool bank and guarded territory within it is discussed. The limits of the territory are assumed to be detined by a possible chase distance. The quick return to perching site is probably provided by sun compass orientation.